Attentional Inhibition in Bilingual Naming Performance: Evidence from Delta-Plot Analyses - Roelofs, Ardi; Piai, Vitória; Garrido Rodriguez, Gabriela (Frontiers in Psychology, 2011)
It has been argued that inhibition is a mechanism of attentional control in bilingual language performance. Evidence suggests that effects of inhibition are largest in the tail of a response time (RT) distribution in non-linguistic and monolingual performance domains. We examined this for bilingual performance by conducting delta-plot analyses of naming RTs. Dutch–English bilingual speakers named pictures using English while trying to ignore superimposed neutral Xs or Dutch distractor words that were semantically related, unrelated, or translations. The mean RTs revealed semantic, translation, and lexicality effects. The delta plots leveled off with increasing RT, more so when the mean distractor effect was smaller as compared with larger. This suggests that the influence of inhibition is largest toward the distribution tail, corresponding to what is observed in other performance domains. Moreover, the delta plots suggested that more inhibition was applied by high- than low-proficiency individuals in the unrelated than the other distractor conditions. These results support the view that inhibition is a domain-general mechanism that may be optionally engaged depending on the prevailing circumstances.